Anion Recoqnition Reactios - Annisa Desfi; Muhammad Zaky; Nessa Zarlita; Velly Effendy; Irfan Ananda Ismail; Munadia Insani (Akademi Akuntansi Indonesia Padang, 2024)
In the recognition of anions there are several anions that are tested so that we can recognize the anions. This praticum aims to be able to analyze various kinds of anions in a sample and write down the reaction. This praticum aims to be able to analyze various kinds of anions in a sample and write down the reaction. Analysis of this anion using the method of organoleptic methods Organoleptic properties are properties that can be measured by the senses, for example, taste, aroma, color, and so on There are several types of anions found in the samples tested. These finding implays indicate the formation of deposits and 2 phases formed during the test.